دور لجان التدقيق في دعم وتحسين حوكمة الشركات - جريو, صارة; بوفليح, نبيل (جامعة الوادي University of Eloued, 2019)
تهدف هذه الورقة البحثية إلى إبراز دور لجنة التدقيق في دعم وتفعيل حوكمة الشركات، باعتبارها لجنة مستقلة منبثقة عن مجلس الإدارة، تقوم بالإشراف على السياسات المحاسبية وإعداد التقارير المالية للمؤسسة والالتزام بتعليماتها، وكذلك تعمل كحلقة وصل بينه وبين كل من المدقق الخارجي والداخلي، كما تعتبر أحد الدعائم الأساسية لنجاح تطبيق حوكمة الشركات من خلال دعم مجلس الإدارة في القيام بأعمال التوجيه والإشراف وتنفيذ مسئولياته القانونية، وبالتالي المساهمة في ضمان جودة التقارير المالية ومصداقية المعلومات المحاسبية. وخلصت نتائج الدراسة إلى وجود تأثير إيجابي لتطبيق مبادئ حوكمة الشركات على الثقة والمصداقية في التقارير المالية في الشركات كما تزيد من فعالية وكفاءة الرقابة على الأنظمة المالية والمحاسبية وتعزز من الثقة في مخرجات هذه الأنظمة المتمثلة بالتقارير المالية. This paper aims to highlight the role of the Audit Committee in supporting and activating corporate governance, as an independent committee of the Board of Directors, which oversees the accounting policies and financial reporting of the institution and complies with its instructions, and acts as a liaison between him and the external and internal auditor, It is also one of the main pillars of the success of the implementation of corporate governance by supporting the Board of Directors in carrying out the work of guidance and supervision and the implementation of its legal responsibilities, and thus contribute to ensure the quality of financial reports and the credibility of accounting information. The results of the study showed that there is a positive impact on the application of the principles of corporate governance to the confidence and credibility in the financial reports of companies and increase the effectiveness and efficiency of control over financial and accounting systems and enhance confidence in the outputs of these systems of financial reports.
The role of audit committees in supporting and improving corporate governance
مقال
Keywords: لجان التدقيق ; حوكمة الشركات ; التقارير المالية ; التدقيق الداخلي ; التدقيق الخارجي